2015
DOI: 10.1016/j.jascer.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Pseudobrookite-type MgTi2O5 water purification filter with controlled particle morphology

Abstract: Pseudobrookite-type oxide-based ceramics, such as Al 2 TiO 5 and MgTi 2 O 5 , have recently been studied as porous ceramic membranes. Here, the effect of LiF doping on the morphology of MgTi 2 O 5 particles is presented in detail. Water purification filters were produced using porous MgTi 2 O 5 , with different particle morphologies. MgCO 3 (basic) and TiO 2 powders with various LiF contents were wet-ball milled, dried, and then, calcined in air at 1100 • C to obtain the MgTi 2 O 5 powders. The powder compacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…CoTi 2 O 5 has been observed to be antiferromagnetic 23 with possible applications in magnetic sensors, and has been studied as a photocatalyst, 24 but other properties are largely unexplored. However, the isostructural phases Al 2 TiO 5 and MgTi 2 O 5 are known for their low thermal conductivity and low thermal expansion, [25][26][27][28][29] and have applications where thermal insulation and thermal shock resistance are required such as in combustion engines [30][31][32][33] and catalyst carriers. [34][35][36] A primary drawback for these materials is their strong anisotropy of thermal expansion, which leads to poor strength due to extensive microcracking.…”
Section: Introductionmentioning
confidence: 99%
“…The effective filtration area was 22 mm in diameter. bacteria-contaminated water [29,30]. The turbidity of the initial suspension was 894.4 NTU.…”
Section: Characterizationmentioning
confidence: 99%
“…Some studies related to membrane recovery were reported [25,27]. We have recently reported ceramics membrane for water purification filters consisting of pseudobrookite-type Al2TiO5 [28] and MgTi2O5 [29], which are well known for low thermal expansion and high thermal shock resistant ceramics. Although anisotropic rod-like grains effectively worked during filtration, the filtration-rate was not sufficient for practical uses, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, backwashing, chemical washing or heating treatment enable to make the ceramics filters using for a longer time than the organic ones. We have recently reported ceramic water-purification filters made of porous pseudobrookite-type Al 2 TiO 5 [18] and MgTi 2 O 5 [19] and pH 10 standard buffer solutions), respectively. The compressive strength was measured for some selected samples with a prismatic shape (typical dimension of ~ 4×4×12 mm) according to the JIS-R1608 standard.…”
Section: Introductionmentioning
confidence: 99%